2005
DOI: 10.1007/s11095-005-8384-4
|View full text |Cite
|
Sign up to set email alerts
|

BCRP Transports Dipyridamole and is Inhibited by Calcium Channel Blockers

Abstract: Dipyridamole and several dihydropyridines are effective BCRP inhibitors, but bepridil, diltiazem, and verapamil are not. We also identified a new BCRP substrate, dipyridamole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
4
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 38 publications
4
80
4
2
Order By: Relevance
“…Digoxin is not a substrate for Bcrp [58], but other studies have indicated that the poor BBB permeability of digoxin is not explained by P-gp alone [11,38]. Verapamil has been used as a P-gp inhibitor in concentrations from 5 to 150 μM [23,[59][60][61], but it has also been shown to inhibit Mrp activity in concentrations of 5-10 μM [45,62] as well as Bcrp activity, although not in the concentration range applied here [63,64]. In our study, 50 μM verapamil lowered the efflux ratio of digoxin to 1.1, whereas the Bcrp inhibitor, Ko 143, had no effect on the digoxin transport indicating that the verapamil inhibition of A-L digoxin transport we observed was due to inhibition of P-gp or Mrp's.…”
Section: Efflux Transporter Activity In Bovine Blood-brain Barrier Momentioning
confidence: 98%
“…Digoxin is not a substrate for Bcrp [58], but other studies have indicated that the poor BBB permeability of digoxin is not explained by P-gp alone [11,38]. Verapamil has been used as a P-gp inhibitor in concentrations from 5 to 150 μM [23,[59][60][61], but it has also been shown to inhibit Mrp activity in concentrations of 5-10 μM [45,62] as well as Bcrp activity, although not in the concentration range applied here [63,64]. In our study, 50 μM verapamil lowered the efflux ratio of digoxin to 1.1, whereas the Bcrp inhibitor, Ko 143, had no effect on the digoxin transport indicating that the verapamil inhibition of A-L digoxin transport we observed was due to inhibition of P-gp or Mrp's.…”
Section: Efflux Transporter Activity In Bovine Blood-brain Barrier Momentioning
confidence: 98%
“…Chenodeoxycholate-3-sulfate [15] 131 Glycodeoxycholate [15] 2.0 Glycoursodeoxycholate [15] 4.1 Cholate [15,54] [15,54] 7.3/13 Deoxycholate [15,54] 5.2-13 Glycochenodeoxycholate [54] 2.0/2.9 Glychodeoxycholate [54] 2.4/5.4 Glycholate [54] 11/21 Taurochenodeoxycholate [15,54] 1.0-6.1 Taurocholate [15,54] 7.3-25 Taurodeoxycholate [15] 4.5-17 Taurourosdeoxycholate [15] 28 Ursodeoxycholate [15,54] 36 [60] Estrone [56] Bisantrene [67] Betamethasone [57] Riboflavin [68] Taurolithocholate sulfate [56] 37 a Cerivastatin [61] Cerivastain [61] 18 Uric acid [69] Vitamin K3 [ [70] Ciprofloxacin [71] Daunorubicin [56] 59 a Daunorubicin [67] Dexamethasone [57] Diclofenac [72] Diclofenac [72] 71-78 Dipyridamole [73] Digoxin [57] Doxorubicin [67,74] Dipyridamole [73] 6.4 a Enrofloxacin [75] Doxorubicin [56,76] Epirubicin [67] Fluvastatin [61] 5.4 Fluvastatin [61,62] Glibenclamide [77] 150 a Glibenclamide …”
Section: Substrates and Inhibitorsmentioning
confidence: 99%
“…Both diltiazem and verapamil had a very weak effect on ABCG2/ BCRP. Zhang et al (19) reported that the inhibitory activity of nicardipine was strong and that of nifedipine was weak. In addition, diltiazem and verapamil were reported to hardly inhibit ABCG2/BCRP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the case of calcium antagonists having a dihydropyridine structure, the side-chain of the dihydropyridine structure affected the inhibitory activity of ABCG2/BCRP, since the side-chains of calcium antagonists with strong inhibitory activity are larger in molecular weight and molecular surface area than those with weak inhibitory activity. Zhang et al (19) suggested that the side-chain of a heterocyclic compound affected the inhibitory activity of ABCG2/ BCRP. Consequently, if calcium antagonists are used as lead compounds, modifying the side-chain binding to the dihydropyridine structure may be a useful strategy for developing inhibitory activity against ABCG2/BCRP.…”
Section: Discussionmentioning
confidence: 99%